(3GdYOO GdeYOhO aj GdeMGVQGJs - (3RcQjG Hf YHO Gddg GdeQGZj, CHh jMji,J (B550 (3g` s ((3Uaj GdOjf Hf eMeO Hf MSf Hf Ydj Hf eMeO Hf CMeO GdNdjdj GdeNRhej s)
(3ChdgG (B:s
(3hbhdg McGjI Yf TYjH Ydjg GdSdGe YqS YeQ Hf GdNWGH (B((3V(B) (3djdI aSeY ZfGkA aj HjJ aJSqhQ Ydjg, s
(3BNQgG (B:s
(3aVMc GdefUhQ hNqdi SHjdg hjdjg aj GdLRA GdKGfj Ef TGA Gddg GdeOM s
(3GfXQ GdLRA GdChd Qbe (B595-597 (3COHs
(3HChdgG JedjcGJ CbOegG SfI (B996(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B182s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B31 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1130s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs